Straw Quality and Success Rate of Artificial Insemination in Ongole Crossbred (PO) with Different Thawing Times - Sulistyo Sulistyo; Fitri Anggraeni (Journal of Sustainable Livestock, 2025)
Artificial insemination (AI) is the technique of injecting semen from a male bull into a female cow's reproductive system without a natural mating. The aim of this study is to address the issue of how the thawing time affects the quality of the straw and the success AI. The study uses a bull batch 20904 L.92 code of 30 frozen semen from Ungaran (BIB) on 30 Ongole Crossbred cattle in Kepil region, Wonosobo, Central Java. Three treatments were applied, with microscopic evaluations to assess post-thawing spermatozoa quality, including motility and viability. Artificial insemination was performed on 30 cows Ongole Crossbred to see the service per conception and conception rate. Treatment T2 achieved maximum motility in 25 seconds, followed by T3 in 35 seconds, and T1 in 15 seconds. Long thawing times significantly affected frozen semen motility, with T2 significantly different from T1 and T3 respectively. Maximum frozen semen viability was achieved at treatment T2, T1, and T1. Long thawing times significantly affected frozen semen viability, with T2 significantly different from T1, T3, and T1. Long thawing times were not significant in post-thawing service per conception and conception rates from three treatments. Thawing for 25 seconds ensures high-quality sperm for successful artificial insemination.